(untitled) (Mongolian Journal of Agricultural Sciences, 2021)
Mongolia has the unique dietary habit having a great deal of animal products especially among rural resident.To capture the status of Mongolian gut microbiome, we characterized bacterial community of 98 healthy Mongolian adults and compared with that of adults in five Asian countries, including Korea, China, Japan, Thailand and Indonesia. Principal component analysis (PCA) was performed based on genus composition of each sample. As a result, three microbiome-type cluster, the so-called “enterotype”, driven by the three taxonomic groups, Prevotella (P-type), Bacteroides and Bifidobacterium (BB-type), and Ruminococcaceae (R-type), were observed. Most of Mongolian subjects harbored P-type, which is known to strongly depend on carbohydrate-based diets. Further, the metagenomic analysis indicated that Catenibacterium and Lactobacillus were enriched in Mongolian subjects which may be concerned with intake of animal-based and dairy products-based diets, respectively. These results suggest that gut microbiome status of Mongolian people associates with the traditional unique dietary habit.